Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

mahamuud18

  • 2 years ago

3+2cos^2(x)=5cos^2(x)+3sin^2(x)

  • This Question is Closed
  1. Mertsj
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Replace sin^2x with 1-cos^2x. Get it equal to 0 and factor.

  2. mahamuud18
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank you

  3. Mertsj
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    yw

  4. jishan
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    3+ 2cos^2x= 5cos^2x+ 3sin^2x lhs= 3+ 2cos^2x = 3( sin^2x+cos^2x) + 2cos^2x =3 sin^2x+3cos^2x + 2cos^2x =5cos^2x+ 3 sin^2x =rhs put sin^2x +cos^2x = 1

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy